Plant density in pineapple culture - Choairy, Salim Abreu; Fernandes, Pedro Dantas (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was conducted at Mari, PB, Brazil, in a podzolic soil, the study the influence of five plant densities of pineapple (Ananas comosus (L.) Merrill) cv. Smooth Cayenne on yield and quality of fruit. The experiment was carried out in a randomized block design with five treatments according to the five different spacings among plants: a. 90 cm x 45 cm x 30 cm (49,380 pl./ha); b. 90 cm x 30 cm x 30 cm (55,555 pl./ha); c. 80 cm x 30 cm x 30 cm (60,600 pl./ha); d. 80 cm x 30 cm x 25 cm (72,070 pl./ha); and e. 80 cm x 30 cm x 20 cm (90,900 pl./ha). It was observed that the fruit yields increased with increasing plant density but did not affect the average of fruit weight. The smallest yield was for the lowest density (a.): 54.14 t/ha; and 90.54 t/ha for the highest one (e.). The fruit and fruit-heart diameters decreased with plant density which influenced in a high incidence of Fusarium (b., c., d., e.) and Tecla basilides (c. and d.) on fruits.